US 9,512,709 Multiphase flow metering system - Henry, M; Casimiro, R (United States Patent and Trademark Office, 2016)
A multi-phase flow metering system for measuring a multi-phase fluid including oil, water, and gas, includes a Coriolis mass flow meter adapted to measure mass flow rate and density of the multi-phase fluid. The system has a water cut meter adapted to measure the water cut of the multi-phase fluid. A processor is configured to determine the oil mass flow rate of the oil, water mass flow rate of the water, and gas mass flow rate of the gas using the mass flow rate and density from the Coriolis meter and the water cut from the water cut meter. The processor is further configured to determine dynamic estimates of the uncertainty of each of the oil mass flow rate, water mass flow rate, and gas mass flow rate.